Discovery Learning Model-based Virtual Lab on Photoelectric Effect Material to Improve Critical Thinking Skills - Ahmad, Liza Septia; Prasetyo, Zuhdan Kun (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
This article provides an overview and explanation of a product in virtual laboratory media based on the development of discovery learning with a focus on the material of the photoelectric effect. The paper also outlines the readability and practicality aspects for both students and teachers in the virtual lab while explaining the effectiveness of the virtual lab in enhancing students' critical thinking skills. The product discussed in this article was developed using the 4D model and scheme. It has undergone expert validation and product testing. The research presented in this article was conducted at two public high schools in Yogyakarta. The study utilized questionnaires, observation sheets, expert validation sheets, readability sheets, practicality sheets, and tests. The research data was analyzed using Gregory's analysis for expert validation and Manova's analysis for field testing. The study results indicate that the virtual lab is deemed appropriate as a learning medium based on expert validation for the photoelectric effect material. From the perspectives of readability and practicality, the developed product falls into the excellent category. This study, using the Manova test, effectively illustrated a substantial enhancement in the critical thinking abilities of students, notably in the areas of analysis, elaborating on concepts, and forming conclusions. Consequently, this paper offers a detailed insight into the creation of novel educational tools and presents robust empirical data supporting their role in improving critical thinking in students, with a specific focus on the subject of the photoelectric effect.